Capacitor, circuit, circuit board and device
By adjusting the cation and anion number ratio in the halide in the dielectric of the capacitor, the relative dielectric constant of the dielectric is improved, and the problems of high manufacturing cost and poor performance of existing capacitors are solved, thereby achieving high capacitance and voltage resistance. promote.
Patent Information
- Application Number
- CN202380043535.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-02
- Publication Date
- 2025-01-10
AI Technical Summary
In terms of miniaturization and high performance, existing capacitors have problems such as high manufacturing cost, low elastic constant and poor durability, especially in the case of high electrostatic capacity halide films.
By adjusting the number ratio of cations and anions in the halide, the relative dielectric constant of the dielectric is increased, thereby increasing the capacitance of the capacitor.
The synthesis of high-static capacitance capacitors at low temperatures is realized, which reduces manufacturing costs and improves the withstand voltage and elastic constant of the capacitors, meeting the needs of miniaturization and high-performance of electronic equipment.
Smart Images

Figure CN119301714A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to capacitors, circuits, circuit boards, and devices. Background Art
[0002] Conventionally, halides have been used in devices such as perovskite solar cells.
[0003] For example, Patent Document 1 describes a ferroelectric memory element in which a ferroelectric layer is sandwiched between a pair of electrodes. The ferroelectric layer contains a predetermined halide-based organic-inorganic hybrid perovskite compound or an inorganic perovskite compound. As the halide-based organic-inorganic hybrid perovskite compound, for example, CH3NH3PbI3, C2H5NH3PbI4, CH3NH3SnI3, and C2H5NH3SnI4 are shown. As the inorganic perovskite compound, CsSnI3 is shown.
[0004] Patent Document 2 describes a ferroelectric device including a ferroelectric element having a pair of opposite surfaces and a pair of electrodes formed on the pair of opposite surfaces. As an example of the material of the main body of the ferroelectric element, CsGeCl3 and BaMgF4 are described.
[0005] Prior Art Documents
[0006] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2016-171152
[0007] Patent Document 2: Japanese Unexamined Patent Application Publication No. 10-93031 Summary of the Invention
[0008] The present disclosure provides a capacitor that uses a dielectric containing a halide and is advantageous from the viewpoint of high electrostatic capacitance.
[0009] The capacitor of the present disclosure includes:
[0010] a first electrode;
[0011] a second electrode; and
[0012] a dielectric disposed between the first electrode and the second electrode,
[0013] the dielectric contains a halide and satisfies the condition of 1 / 2 < r < 2 / 3, <00
[0016] Figure 1 This is a cross-sectional view showing an example of the capacitor disclosed herein.
[0017] Figure 2 This is a graph showing the relationship between the calculated value of the relative dielectric constant of PbS and the volume of the coordination polyhedron in PbS having various coordination polyhedra.
[0018] Figure 3A It is a diagram showing a coordination polyhedron of a ZnS type crystal structure.
[0019] Figure 3B It is a diagram showing a coordination polyhedron of a NaCl-type crystal structure.
[0020] Figure 3C It is a diagram showing a coordination polyhedron of a CuS type crystal structure.
[0021] Figure 4A This is a cross-sectional view showing another example of the capacitor disclosed herein.
[0022] Figure 4B This is a cross-sectional view showing another example of the capacitor disclosed herein.
[0023] Figure 4C This is a cross-sectional view showing another example of the capacitor disclosed herein.
[0024] Figure 5A This is a diagram schematically showing an example of a circuit of the present disclosure.
[0025] Figure 5B This is a diagram schematically showing an example of a circuit board according to the present disclosure.
[0026] Figure 5C This is a diagram schematically showing an example of the device disclosed herein.
[0027] Figure 6 It is a diagram schematically showing a method for evaluating the relative dielectric constant of dielectrics in each Example and each Comparative Example.
[0028] Figure 7 This is a graph showing the X-ray diffraction (XRD) pattern of the dielectric material of Example 1.
[0029] Figure 8 This is a graph showing the XRD pattern of the dielectric material of Comparative Example 2.
[0030] Figure 9 This is a diagram showing the crystal structure of perovskite-type (CH3NH3)SnCl3.
[0031] Figure 10This is a diagram showing the crystal structure of (NH4)Pb2Br5 type KSn2Cl5. DETAILED DESCRIPTION
[0032] (Insights that form the basis of this disclosure)
[0033] In recent years, with the miniaturization and high functionality of electronic devices, the miniaturization, high integration and high frequency of electronic circuits have been continuously promoted. Regarding electronic components used in electronic circuits, miniaturization and high performance are also required. For example, it is believed that if a small capacitor with high electrostatic capacitance can be provided, it can contribute to the miniaturization and high performance of electronic components. The electrostatic capacitance depends on the relative dielectric constant of the dielectric used for the capacitor. The higher the relative dielectric constant, the greater the electrostatic capacitance. Capacitors using oxide dielectrics as dielectrics showing high relative dielectric constants have been widely developed. However, in order to synthesize oxides, it is usually necessary to sinter them at a high temperature of 500°C or above, which easily increases the manufacturing cost of the capacitor. In addition, in most cases, the elastic constant of the oxide is small, making it difficult to increase the filling rate of the pressed powder. Therefore, it is difficult to improve the performance of the capacitor. In addition, it is difficult for oxides to have high strength against bending stress.
[0034] Halides have the potential to eliminate these shortcomings of oxides. Halides generally have high solubility in water and organic solvents, making them easy to synthesize by coating methods. Furthermore, since halides can be synthesized at low temperatures, below 200°C, it is expected that the manufacturing cost of capacitors will be reduced. Furthermore, halide films can be formed on substrates such as films that are not highly resistant to high temperatures, potentially enabling the realization of flexible capacitors. Furthermore, since the elastic constants of halides are generally higher than those of oxides, it is easy to increase the filling rate of pressed powders. However, it is also believed that due to the low relative dielectric constant of halides at room temperature, the high electrostatic capacitance of oxide dielectrics cannot be expected.
[0035] In light of this situation, the present inventors have conducted extensive research to develop a capacitor that utilizes a dielectric containing a halide and exhibits advantages from the perspective of high capacitance. As a result, the present inventors have discovered that the dielectric constant of the dielectric can be easily increased by preparing the dielectric so that the number of anions and cations in the halide satisfies specified conditions. Based on this new knowledge, the present inventors have developed the capacitor disclosed herein.
[0036] (Overview of One Embodiment of the Present Disclosure)
[0037] A first aspect of the present disclosure provides a capacitor including:
[0038] a first electrode;
[0039] A second electrode; and
[0040] a dielectric disposed between the first electrode and the second electrode,
[0041] where the dielectric contains a halide and satisfies the condition of 1 / 2 < r < 2 / 3,
[0042] in the condition, r is the ratio of the number of cations to the number of anions in the halide.
[0043] According to the first aspect, the coordination number of anions around the cation is likely to increase, and the dielectric is likely to have a high relative dielectric constant. Therefore, the capacitor is likely to have a high electrostatic capacitance.
[0044] In the second aspect of the present disclosure, for example, in the capacitor according to the first aspect, the dielectric may also satisfy the condition of 0.57 ≤ r ≤ 0.61. According to the second aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0045] In the third aspect of the present disclosure, for example, in the capacitor according to the first aspect or the second aspect, the cation may also contain ions of elements selected from at least one of Group 13, Group 14, and Group 15. According to the third aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0046] In the fourth aspect of the present disclosure, for example, in the capacitor according to the third aspect, the cation may also have a lone pair of electrons. According to the fourth aspect, the electrons constituting the lone pair of electrons are difficult to bind to surrounding ions. Therefore, the electronic state in the cation is likely to become unstable, and the dielectric is likely to have a desired crystal structure. As a result, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0047] In the fifth aspect of the present disclosure, for example, in the capacitor according to any one of the first aspect to the fourth aspect, the cation may also contain at least one selected from In + , Tl + , Ge 2+ , Sn 2+ , Pb 2+ , Sb 3+ and Bi 3+ . According to the fifth aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0048] In the sixth aspect of the present disclosure, for example, in the capacitor according to any one of the first aspect to the fifth aspect, it may also contain at least one selected from Li +、Na + , K + , Rb + 、Cs + 、In + and Tl + According to the sixth aspect, the dielectric material is more likely to have a high relative permittivity, and the capacitor is more likely to have a high electrostatic capacitance.
[0049] In the seventh aspect of the present disclosure, for example, in the capacitor according to any one of the first to sixth aspects, the dielectric may have a composition represented by AB2X5. In the composition, A may be selected from Li + 、Na + , K + , Rb + 、Cs + 、In + and Tl + At least one of. B can also be selected from Sn 2+ and Pb 2+ At least one of. X can also be selected from F - 、Cl - Br - , I - and SCN - According to the seventh aspect, the dielectric material is more likely to have a high relative permittivity, and the capacitor is more likely to have a high electrostatic capacitance.
[0050] In the eighth aspect of the present disclosure, for example, in the capacitor according to any one of the first to seventh aspects, the anion may be selected from F - and Cl - According to the eighth aspect, the dielectric breakdown electric field of the dielectric is likely to be increased, and the capacitor is likely to have high withstand voltage.
[0051] A circuit according to a ninth aspect of the present disclosure includes the capacitor according to any one of the first to eighth aspects. According to the ninth aspect, the capacitor easily has a high capacitance, and the circuit easily exhibits desired performance.
[0052] A circuit board according to a tenth aspect of the present disclosure includes the capacitor according to any one of aspects 1 to 8. According to the tenth aspect, the capacitor easily has a high electrostatic capacitance, and the circuit board easily exhibits desired performance.
[0053] The device according to the 11th aspect of the present disclosure includes the capacitor according to any one of the 1st to 8th aspects. According to the 11th aspect, the capacitor easily has a high electrostatic capacitance, and the device easily exhibits desired performance.
[0054] (Embodiment)
[0055] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. The present disclosure is not limited to the following embodiments.
[0056] Figure 1 is a cross-sectional view showing an example of the capacitor of the present disclosure. As Figure 1 shown, the capacitor 1a includes a first electrode 11, a second electrode 12, and a dielectric 20. The dielectric 20 is disposed between the first electrode 11 and the second electrode 12. The dielectric 20 contains a halide and satisfies the condition of 1 / 2 < r < 2 / 3. In this condition, r is the ratio of the number of cations to the number of anions in the halide. The dielectric 20 contains, for example, an ionic crystal.
[0057] Figure 2 is a graph showing the relationship between the calculated relative dielectric constant of PbS and the volume of the coordination polyhedron in PbS having various coordination polyhedra. The calculated relative dielectric constant of this PbS is obtained by first-principles calculation. Figure 2 Each mark in the graph of represents a compound corresponding to the crystal structure used as a prototype in the first-principles calculation. In Figure 2 , ZnS is zinc sulfide, BN is boron nitride, NiAs is nickel arsenide, NaCl is sodium chloride, TlI is thallium iodide, and CuS is copper(II) sulfide. Figure 3A is a diagram showing the coordination polyhedron of the ZnS-type crystal structure, Figure 3B is a diagram showing the coordination polyhedron of the NaCl-type crystal structure, Figure 3C is a diagram showing the coordination polyhedron of the CuS-type crystal structure. As Figure 3A shown, in the ZnS-type crystal structure, S 2- coordinates in such a manner as to form a tetrahedron (4 coordination) centered on Pb 2+ . As Figure 3B shown, in the NaCl-type crystal structure, S 2- coordinates in such a manner as to form an octahedron (6 coordination) centered on Pb 2+ . As Figure 3C shown, in the CuS-type crystal structure, S 2- coordinates in such a manner as to form a trigonal pyramid column (7 coordination) centered on Pb 2+ . It can be understood from Figure 2 that if the coordination number is large, the volume of the coordination polyhedron is large. Therefore, according to Figure 2 , if the cation Pb 2+ and the anion S 2-If the coordination number is large, the relative dielectric constant of PbS will become high. This is considered to be because when the coordination number is large, the volume of the coordination polyhedron becomes large, the region where ions can move becomes large, and the local polarization becomes large. Further, it is considered that the coordination number of anions around a cation has a greater influence on the relative dielectric constant than the coordination number of cations around an anion. The reason is that the absolute value of the valence of a cation is larger than that of an anion, and larger polarization is more likely to occur. For example, in TiO2, the anion O 2- has a valence of -2, but the cation Ti 4+ has a valence of +4. Therefore, it is considered that a material having a crystal structure with a large coordination number of anions around a cation has a high relative dielectric constant. In order to achieve a structure with a large coordination number of anions around a cation, a composition in which the ratio of the number of cations to the number of anions in the halide contained in the dielectric is small is advantageous.
[0058] Since the dielectric 20 satisfies the condition of r < 2 / 3, in the halide contained in the dielectric 20, the ratio of the number of cations to the number of anions is small. Therefore, the coordination number of anions around a cation is likely to increase, and the dielectric 20 is likely to have a high relative dielectric constant. As a result, the capacitor 1a is likely to have a high electrostatic capacitance. In addition, by satisfying the condition of 1 / 2 < r in the dielectric 20, it is easy to obtain a local structure with a high coordination number in the dielectric 20, and a desired crystal structure can be formed, and the dielectric 20 is likely to have a high relative dielectric constant.
[0059] In the dielectric 20, the condition of r ≤ 0.66 can be satisfied, the condition of r ≤ 0.65 can be satisfied, the condition of r ≤ 0.64 can be satisfied, the condition of r ≤ 0.63 can be satisfied. The condition of r ≤ 0.62 can be satisfied, the condition of r ≤ 0.61 can be satisfied, the condition of r ≤ 0.60 can be satisfied.
[0060] In the dielectric 20, the condition of 0.51 ≤ r can be satisfied, the condition of 0.52 ≤ r can be satisfied, the condition of 0.53 ≤ r can be satisfied, the condition of 0.54 ≤ r can be satisfied. The condition of 0.55 ≤ r can be satisfied, the condition of 0.56 ≤ r can be satisfied, the condition of 0.57 ≤ r can be satisfied.
[0061] The dielectric 20 preferably satisfies the condition of 0.57 ≤ r ≤ 0.61. In this case, the dielectric 20 is more likely to have a high relative dielectric constant, and the capacitor 1a is more likely to have a high electrostatic capacitance.
[0062] The cations in dielectric 20 are not limited to specific cations. For example, the cations may include ions of elements from at least one of Groups 13, 14, and 15 of the periodic table. In this case, dielectric 20 is more likely to have a high relative dielectric constant, and capacitor 1a is more likely to have a high electrostatic capacitance.
[0063] The cations in the dielectric 20 have, for example, lone electron pairs. A lone electron pair is an electron pair formed by two electrons belonging to a specific atom and is not shared with other atoms. For example, the ion Sn of Sn, which is a Group 14 element, 2+ Has a lone electron pair. Sn 2+ The two electrons that fill the outermost s orbital form a lone electron pair by taking away two electrons from Sn. The electrons that form the lone electron pair are difficult to combine with the surrounding ions, which can lead to unstable electronic states or special crystal structures. Therefore, if the cations in the dielectric 20 have lone electron pairs, the relative dielectric constant of the dielectric 20 tends to be high. On the other hand, as Sn ions, in addition to Sn 2+ Sn can also exist 4+ . Sn 4+ It is formed by taking away 4 electrons from Sn, and the outermost s orbital becomes empty. 4+ In this case, a crystal structure with a low coordination number is easily formed, and the relative dielectric constant of the material is difficult to increase.
[0064] For example, all the cations in the dielectric 20 may have lone electron pairs, or only some of the cations in the dielectric 20 may have lone electron pairs.
[0065] The cations in the dielectric 20 include, for example, In + 、Tl + 、Ge 2+ 、Sn 2+ , Pb 2+ 、Sb 3+ and Bi 3+ In this case, the dielectric 20 is more likely to have a high relative dielectric constant, and the capacitor 1a is more likely to have a high electrostatic capacitance. The cations in the dielectric 20 may also be selected from In + 、Tl + 、Ge 2+ 、Sn 2+ , Pb 2+ 、Sb 3+ and Bi 3+ At least one of them may have cations other than these.
[0066] The cations in the dielectric 20 include, for example, Li+ 、 Na + 、 K + 、 Rb + 、 Cs + 、 In + and Tl + At least one of them. In this case, the dielectric 20 is more likely to have a high relative dielectric constant, and the capacitor 1a is more likely to have a high electrostatic capacitance.
[0067] As long as the dielectric 20 contains a halide and satisfies the condition of 1 / 2 < r < 2 / 3, the anion in the halide is not limited to a specific anion. The halide contained in the dielectric 20 may contain only halogen ions as anions, or may contain anions other than halogen ions. The anion in the halide may be, for example, selected from F - and Cl - At least one of them. In this case, the band gap of the dielectric 20 is likely to increase, and the dielectric breakdown electric field of the dielectric 20 is likely to increase. Therefore, the capacitor 1a is likely to have a high withstand voltage. The halide contained in the dielectric 20 may also contain only at least one of F - and Cl - as an anion. In this case, the band gap of the dielectric 20 is more likely to increase, and the dielectric breakdown electric field of the dielectric 20 is more likely to increase. The halide contained in the dielectric 20 may also contain, while including at least one of F - and Cl - at least one of them, an anion other than F - and Cl - 以外的阴离子。
[0068] The composition of the dielectric 20 is not limited to a specific composition as long as it satisfies the condition of 1 / 2 < r < 2 / 3. The dielectric 20 has, for example, a composition represented by AB2X5. In this composition, A is selected from Li + 、 Na + 、 K + 、 Rb + 、 Cs + 、 In + and Tl + At least one of them. B is selected from Sn 2+ and Pb 2+ At least one of them. X is selected from F - 、 Cl - 、 Br - 、 I - and SCN - At least one of them. When the dielectric 20 has such a composition, the dielectric 20 is more likely to have a high relative dielectric constant, and the capacitor 1a is more likely to have a high electrostatic capacitance.
[0069] Typically, in the above composition, the dielectric 20 comprises a material selected from F - 、Cl - Br - and I - At least one of them is used as X.
[0070] The relative dielectric constant of dielectric 20 is not limited to a specific value. The relative dielectric constant of dielectric 20 at room temperature at 1 MHz can be, for example, higher than 40, 45 or higher, 50 or higher, 60 or higher, 80 or higher, or 100 or higher. Room temperature is, for example, a specific temperature within the range of 20°C to 25°C. The relative dielectric constant of dielectric 20 at room temperature at 1 MHz is, for example, 10,000 or lower. In other words, the relative dielectric constant of dielectric 20 at room temperature at 1 MHz is, for example, 40 or higher and 10,000 or lower.
[0071] like Figure 1 As shown, in capacitor 1a, dielectric 20 is formed as a film, for example. The method of configuring dielectric 20 in capacitor 1a is not limited to a specific method. Dielectric 20 can be formed by, for example, spin coating, inkjet, die coating, roller coating, rod coating, Langmuir-Blodgett method, dip coating or spray coating. As a result, dielectric 20 is more likely to have a high relative dielectric constant, and capacitor 1a is more likely to have a high electrostatic capacitance. Dielectric 20 can also be formed by sputtering, anodization, vacuum evaporation, pulsed laser deposition (PLD), atomic layer deposition (ALD) or chemical vapor growth (CVD).
[0072] like Figure 1 As shown, the dielectric 20 is disposed between the first electrode 11 and the second electrode 12 in the thickness direction of the dielectric 20 , for example. The second electrode 12 covers at least a portion of the dielectric 20 , for example.
[0073] The materials constituting the first electrode 11 and the second electrode 12 are not limited to a specific material. The first electrode 11 and the second electrode 12 each comprise, for example, a metal. The first electrode 11 comprises, for example, a valve metal. Examples of valve metals are Al, Ta, Nb, and Bi. The first electrode 11 comprises, for example, at least one selected from Ta, Nb, and Bi as a valve metal. The first electrode 11 may comprise a precious metal such as gold or platinum, may comprise nickel, or may comprise a metal element from Group 13, Group 14, or Group 15.
[0074] The second electrode 12 may include, for example, a valve metal such as Al, Ta, Nb, or Bi; a noble metal such as gold, silver, or platinum; nickel; or a metal element from Group 13, Group 14, or Group 15. For example, the second electrode 12 includes at least one selected from the group consisting of Al, Ta, Nb, Bi, gold, silver, platinum, and nickel.
[0075] like Figure 1 As shown, the first electrode 11 has a main surface 11p. One main surface of the dielectric 20 is in contact with the main surface 11p, for example. The second electrode 12 has a main surface 12p parallel to the main surface 11p. The other main surface of the dielectric 20 is in contact with the main surface 12p, for example.
[0076] Figure 4A This is a cross-sectional view showing another example of the capacitor disclosed herein. Figure 4A Capacitor 1b shown is constructed similarly to capacitor 1a, except for the parts specifically described. Components of capacitor 1b that are identical or corresponding to those of capacitor 1a are denoted by the same reference numerals, and detailed descriptions are omitted. The descriptions regarding capacitor 1a also apply to capacitor 1b, provided they are not technically inconsistent. Furthermore, these descriptions also apply to capacitors 1c and 1d, described later.
[0077] Figure 4A The capacitor 1b shown is an electrolytic capacitor. Figure 4A As shown, in capacitor 1b, at least a portion of first electrode 11 is porous. This configuration easily increases the surface area of first electrode 11, and capacitor 1b tends to have a higher capacitance. This porous structure can be formed, for example, by etching metal foil or sintering powder.
[0078] like Figure 4A As shown, for example, a film of dielectric 20 is formed on the surface of the porous portion of first electrode 11. Methods for forming dielectric 20 include spin coating, inkjet coating, die coating, roller coating, bar coating, Langmuir-Blodgett method, dip coating, or spray coating. Dielectric 20 can also be formed by, for example, sputtering, anodization, vacuum evaporation, PLD, ALD, or CVD.
[0079] The first electrode 11 includes, for example, a valve metal such as Al, Ta, Nb, Zr, Hf, or Bi. The second electrode 12 may include, for example, a solidified silver-containing paste, a carbon material such as graphite, or both.
[0080] In capacitor 1b, for example, electrolyte 13 is disposed between first electrode 11 and second electrode 12. Specifically, electrolyte 13 is disposed between dielectric 20 and second electrode 12. In capacitor 1b, second electrode 12 and electrolyte 13 constitute, for example, a cathode. In capacitor 1b, electrolyte 13 is disposed, for example, to fill the gaps around the porous portion of first electrode 11.
[0081] Electrolyte 13 comprises, for example, at least one selected from an electrolyte solution and a conductive polymer. Examples of conductive polymers include polypyrrole, polythiophene, polyaniline, and their derivatives. Electrolyte 13 may also be a manganese compound such as manganese oxide. Electrolyte 13 may also comprise a solid electrolyte.
[0082] Electrolyte 13 containing a conductive polymer can be formed by chemically polymerizing, electrolytically polymerizing, or both chemically and electrolytically polymerizing raw material monomers on dielectric 20. Electrolyte 13 containing a conductive polymer can also be formed by attaching a solution or dispersion of the conductive polymer to dielectric 20.
[0083] Figure 4B : is a cross-sectional view showing another example of the capacitor disclosed in the present invention. Figure 4B In the illustrated capacitor 1c, at least a portion of the first electrode 11 is porous. This configuration increases the surface area of the first electrode 11, allowing the capacitor 1c to have a higher capacitance. This porous structure can be formed, for example, by etching metal foil or sintering powder.
[0084] like Figure 4B As shown, for example, a film of dielectric 20 is formed on the porous portion of first electrode 11. Methods for forming dielectric 20 include spin coating, inkjet coating, die coating, roller coating, bar coating, Langmuir-Blodgett method, dip coating, or spray coating. In capacitor 1d, dielectric 20 is disposed, for example, to fill the gaps surrounding the porous portion of first electrode 11.
[0085] Figure 4C : is a cross-sectional view showing another example of the capacitor disclosed in the present invention. Figure 4C In the capacitor 1d shown, the dielectric 20 is formed, for example, as a film. A different dielectric 22 from the dielectric 20 is dispersed within the film. Methods for forming the film include spin coating, inkjet coating, die coating, roller coating, rod coating, the Langmuir-Blodgett method, dip coating, or spray coating. For example, by forming a coating of a precursor solution containing the raw materials of the dielectric 20 and particles of the different dielectric 22 using the aforementioned methods, a film containing the dielectric 20 and the different dielectric 22 can be obtained. The film can also be formed by sputtering, anodization, vacuum evaporation, PLD, ALD, or CVD.
[0086] The heterogeneous dielectric 22 is not limited to a specific dielectric as long as it is a different type of dielectric from the dielectric 20. For example, the heterogeneous dielectric 22 has a relative dielectric constant higher than that of the dielectric 20. For example, the heterogeneous dielectric 22 may be a perovskite compound such as BaTiO3, PbTiO3, or SrTiO3, or a layered perovskite compound. The heterogeneous dielectric 22 may also include at least one selected from the group consisting of a Ruddlesden-Popper compound, a Dion-Jacobson compound, a tungsten bronze compound, and a pyrochlore compound.
[0087] The size of the particles of the different dielectric material 22 is not limited to a specific value. The particles of the different dielectric material 22 have a size of, for example, 1 nm or more and 100 nm or less.
[0088] Figure 5A This figure schematically illustrates an example of a circuit disclosed herein. Circuit 3 includes capacitor 1a. Circuit 3 can be either an active or passive circuit. Circuit 3 can be a discharge circuit, a smoothing circuit, a decoupling circuit, or a coupling circuit. Because circuit 3 includes capacitor 1a, circuit 3 can easily achieve the desired performance. For example, capacitor 1a facilitates noise reduction in circuit 3. Circuit 3 can also include capacitors 1b, 1c, or 1d in place of capacitor 1a.
[0089] Figure 5B Schematically shows an example of a circuit board of the present disclosure. Figure 5B As shown, circuit board 5 includes capacitor 1a. For example, circuit board 5 includes circuit 3 including capacitor 1a. Circuit board 5 can be an embedded board or a motherboard. Circuit board 5 can also include capacitors 1b, 1c, or 1d instead of capacitor 1a.
[0090] Figure 5C Schematically shows an example of the device disclosed in the present invention. Figure 5CAs shown, device 7 includes, for example, a capacitor 1a. Device 7 includes, for example, a circuit board 5 including capacitor 1a. Since device 7 includes capacitor 1a, device 7 can easily exhibit desired performance. Device 7 can be an electronic device, a communication device, a signal processing device, or a power supply device. Device 7 can be a server, an AC adapter, an accelerator, or a flat-panel display device such as a liquid crystal display (LCD). Device 7 can be a USB charger, a solid-state drive (SSD), an information terminal such as a PC, a smartphone, or a tablet PC, or an Ethernet switch.
[0091] Example
[0092] Hereinafter, the present disclosure will be described in more detail by way of examples. Note that the following examples are for illustration only and the present disclosure is not limited to the following examples.
[0093] <Example 1>
[0094] (Manufacturing of Dielectric Materials)
[0095] In an argon atmosphere with a dew point below -60°C (hereinafter referred to as a "dry argon atmosphere"), raw material powders containing KCl and SnCl₂ were prepared so that the ratio of KCl to SnCl₂ was 1:2. This raw material powder was crushed and mixed in a mortar. This yielded a mixed powder. The mixed powder was milled using a planetary ball mill at 500 rpm (revolutions per minute) for 12 hours. This yielded the powdered dielectric of Example 1. The dielectric of Example 1 contained a halide having a composition represented by KSn₂Cl₅.
[0096] The dielectric of Example 1 was subjected to XPS analysis using a PHI VersaProbe2 X-ray photoelectron spectroscopy (XPS) instrument manufactured by ULVAC PHI. The K, Sn, and Cl contents per unit weight of the dielectric were determined based on the results. Based on the K, Sn, and Cl contents, the dielectric of Example 1 exhibited the same K:Sn:Cl ratio as in the raw material powder: 1:2:5.
[0097] (Evaluation of relative dielectric constant)
[0098] Figure 6 This is a diagram schematically showing the evaluation method of relative dielectric constant. Figure 6As shown, the press forming die 30 includes a punch upper portion 31, a frame die 32, and a punch lower portion 33. The punch upper portion 31 and the punch lower portion 33 are each formed of stainless steel having electronic conductivity. The frame die 32 is formed of polycarbonate having electrical insulation properties.
[0099] The relative dielectric constant of the halide contained in the dielectric of Example 1 was measured using the press molding die 30 by the following method.
[0100] In a dry atmosphere with a dew point of -30°C or less, the powdered dielectric of Example 1 was filled into a press die 30 to obtain a sample Sa. Inside the press die 30, a pressure P of 300 MPa was applied to the sample Sa using the upper punch 31 and the lower punch 33.
[0101] While applying pressure P to the sample Sa, the upper portion 31 of the punch and the lower portion 33 of the punch are connected to a potentiostat 50 equipped with a frequency response analyzer. As the potentiostat 50, VersaSTAT4 manufactured by Princeton Applied Research was used. The upper portion 31 of the punch is connected to the working electrode and the potential measurement terminal of the potentiostat 50. The lower portion 33 of the punch is connected to the counter electrode and the reference electrode of the potentiostat 50. The impedance of the sample Sa was measured by electrochemical impedance spectroscopy at room temperature (25°C). The relative dielectric constant ε of the halide contained in the dielectric of Example 1 at 1 MHz was measured as follows. ’ r The electrostatic capacitance of each sample was measured, and the relative dielectric constant ε was determined based on the measured electrostatic capacitance value, the thickness of the sample Sa, and the electrode area. ’ r The relative dielectric constant ε is calculated using the following formula using the filling rate f of the pellet (the sample Sa compressed under pressure P): ’ r After correction, the relative dielectric constant ε is obtained r In the following formula, ε Air is the relative dielectric constant of the atmosphere. In this calculation, ε Air Set to 1.
[0102] logε r =(logε ’ r -(1-f)*logε Air ) / f
[0103] The filling rate f is calculated by the following formula. pelletis the density of the tablet, and ρ is the density obtained from the crystal structure. The results are shown in Table 1. As shown in Table 1, the relative dielectric constant ε of the halide contained in the dielectric of Example 1 measured at 25°C is r It is 119.
[0104] f=ρ pellet / ρ
[0105] (Polarized Evaluation)
[0106] Based on the relative dielectric constant ε determined in the above-mentioned evaluation of the relative dielectric constant r , the calculated value of the polarization P of the dielectric of Example 1 is calculated by the following formula (1). The results are shown in Table 1. In formula (1), ε0 is the dielectric constant of vacuum, and E is the insulation breakdown electric field. The insulation breakdown electric field E refers to Wang Li-Mo. "Relationship between intrinsic breakdown field and bandgap of materials." 2006 25th International Conference on Microelectronics. IEEE, 2006. (Wang, Li-Mo. "Relationship between intrinsic breakdown field and bandgap of materials." 2006 25th International Conference on Microelectronics. IEEE, 2006.), and is calculated by the following formula (2). In formula (2), E g is the band gap, and is assumed to be 4 eV in this calculation. E and E in equations (1) and (2) g The units are V / cm and eV respectively.
[0107] P = ε0(ε r -1)E formula (1)
[0108] E = 1.36 × 10 7 ×(E g / 4) Formula (2)
[0109] (Crystal Structure Analysis)
[0110] X-ray diffraction (XRD) measurement was performed to identify the crystal structure of the dielectric of Example 1. In this measurement, Cu-Kα rays were used as X-rays, and the measurement was performed in a dry argon atmosphere. Figure 7 This is a graph showing the XRD pattern of the dielectric of Example 1. The horizontal axis represents the diffraction angle 2θ, and the vertical axis represents the intensity of X-ray diffraction. Figure 7 The calculation results of the XRD patterns of KCl, SnCl2 and (NH4)Pb2Br5 type KSn2Cl5 are shown in FIG. Figure 7The vertical axis in FIG shows the relative relationship of diffraction intensities in each XRD pattern, and does not show the relative relationship of diffraction intensities in different XRD patterns. The XRD pattern of the dielectric of Example 1 shows that the dielectric has a (NH4)Pb2Br5 type crystal structure.
[0111] <Example 2>
[0112] The powdered dielectric of Example 2 was produced in the same manner as in Example 1, except that a raw material powder containing KBr and SnCl₂ was prepared so as to satisfy the condition of the amount of KBr:the amount of SnCl₂=1:2. The composition of the dielectric of Example 2 was determined by XPS measurement in the same manner as in Example 1. Furthermore, the dielectric of Example 2 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0113] <Example 3>
[0114] A powdered dielectric of Example 3 was produced in the same manner as in Example 1, except that a raw material powder containing KBr and SnBr2 was prepared so as to satisfy the condition of KBr molar mass:SnBr2 molar mass = 1:2. The composition of the dielectric of Example 3 was determined by XPS analysis in the same manner as in Example 1. Furthermore, the dielectric of Example 3 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0115] <Example 4>
[0116] The powdered dielectric of Example 4 was prepared in the same manner as in Example 1 except that the raw material powder containing K(SCN) and SnCl2 was prepared so as to satisfy the condition of the amount of substance of K(SCN):the amount of substance of SnCl2=1:2. - It is a cluster anion with a valence of -1 and is considered as SCN - The composition of the dielectric of Example 4 was determined based on XPS measurement in the same manner as in Example 1. Furthermore, the dielectric of Example 4 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0117] <Example 5>
[0118] A powdered dielectric of Example 5 was produced in the same manner as in Example 1, except that a raw material powder containing KCl and SnBr2 was prepared so as to satisfy the condition of the amount of KCl:the amount of SnBr2 = 1:2. The composition of the dielectric of Example 5 was determined by XPS measurement in the same manner as in Example 1. Furthermore, the dielectric of Example 5 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0119] <Example 6>
[0120] A powdered dielectric of Example 6 was produced in the same manner as in Example 1, except that a raw material powder containing KI and SnCl₂ was prepared so as to satisfy the condition of KI mass:SnCl₂ mass = 1:2. The composition of the dielectric of Example 6 was determined by XPS analysis in the same manner as in Example 1. Furthermore, the dielectric of Example 6 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0121] <Example 7>
[0122] A powdered dielectric of Example 7 was produced in the same manner as in Example 1, except that a raw material powder containing KCl and PbCl₂ was prepared so as to satisfy the condition of KCl mass:PbCl₂ mass = 1:2. The composition of the dielectric of Example 7 was determined by XPS measurement in the same manner as in Example 1. Furthermore, the dielectric of Example 7 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0123] <Example 8>
[0124] A powdered dielectric of Example 8 was produced in the same manner as in Example 1, except that raw material powders containing KF, KCl, and SnCl₂ were prepared to satisfy the conditions of the amount of KF: amount of KCl: amount of SnCl₂ = 0.5:0.5:2. The composition of the dielectric of Example 8 was determined by XPS analysis in the same manner as in Example 1. Furthermore, the dielectric of Example 8 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0125] <Example 9>
[0126] A powdered dielectric of Example 9 was produced in the same manner as in Example 1, except that raw material powders containing KF, KCl, and PbCl₂ were prepared to satisfy the conditions of KF mass: KCl mass: PbCl₂ mass = 0.5:0.5:2. The composition of the dielectric of Example 9 was determined by XPS analysis in the same manner as in Example 1. Furthermore, the dielectric of Example 9 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0127] <Example 10>
[0128] A powdered dielectric of Example 10 was produced in the same manner as in Example 1, except that a raw material powder containing KI and SnI2 was prepared so as to satisfy the condition of KI amount of substance: SnI2 amount of substance = 1:2. The composition of the dielectric of Example 10 was determined by XPS measurement in the same manner as in Example 1. Furthermore, the dielectric of Example 10 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0129] <Example 11>
[0130] A powdered dielectric of Example 11 was produced in the same manner as in Example 1, except that raw material powders containing KCl, SnCl, and PbCl were prepared so as to satisfy the conditions of the amount of KCl: the amount of SnCl: the amount of PbCl = 1:1:1. The composition of the dielectric of Example 11 was determined by XPS analysis in the same manner as in Example 1. Furthermore, the dielectric of Example 11 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0131] <Example 12>
[0132] A powdered dielectric of Example 12 was produced in the same manner as in Example 1, except that a raw material powder containing NaF and SnF2 was prepared so as to satisfy the condition of the amount of NaF:the amount of SnF2 = 1:2. The composition of the dielectric of Example 12 was determined by XPS measurement in the same manner as in Example 1. Furthermore, the dielectric of Example 12 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0133] <Example 13>
[0134] A powdered dielectric of Example 13 was produced in the same manner as in Example 1, except that a raw material powder containing RbCl and PbCl₂ was prepared so as to satisfy the condition of the amount of RbCl:the amount of PbCl₂=1:2. The composition of the dielectric of Example 13 was determined by XPS analysis in the same manner as in Example 1. The dielectric of Example 13 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0135] <Example 14>
[0136] A powdered dielectric of Example 14 was produced in the same manner as in Example 1, except that a raw material powder containing RbCl and SnCl₂ was prepared so as to satisfy the condition of the amount of RbCl:the amount of SnCl₂ = 1:2. The composition of the dielectric of Example 14 was determined by XPS measurement in the same manner as in Example 1. The dielectric of Example 14 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0137] <Example 15>
[0138] A powdered dielectric of Example 15 was produced in the same manner as in Example 1, except that raw material powders containing CsCl and PbCl₂ were prepared so as to satisfy the condition of CsCl:PbCl₂ mass ratio of 1:2.5. The composition of the dielectric of Example 15 was determined by XPS analysis in the same manner as in Example 1. The dielectric of Example 15 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0139] <Example 16>
[0140] A powdered dielectric of Example 16 was produced in the same manner as in Example 1, except that a raw material powder containing CsCl and PbCl₂ was prepared so as to satisfy the condition of the amount of CsCl:the amount of PbCl₂=1:2. The composition of the dielectric of Example 16 was determined by XPS measurement in the same manner as in Example 1. The dielectric of Example 16 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0141] <Example 17>
[0142] A powdered dielectric of Example 17 was produced in the same manner as in Example 1, except that a raw material powder containing CsBr and SnCl₂ was prepared so as to satisfy the condition of the amount of CsBr:the amount of SnCl₂=1:2. The composition of the dielectric of Example 17 was determined by XPS measurement in the same manner as in Example 1. The dielectric of Example 17 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0143] <Example 18>
[0144] A powdered dielectric of Example 18 was produced in the same manner as in Example 1, except that a raw material powder containing CsCl and SnCl₂ was prepared so as to satisfy the condition of the amount of CsCl:the amount of SnCl₂ = 1:2. The composition of the dielectric of Example 18 was determined by XPS measurement in the same manner as in Example 1. The dielectric of Example 18 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0145] <Example 19>
[0146] A powdered dielectric of Example 19 was produced in the same manner as in Example 1, except that a raw material powder containing InI and SnCl₂ was prepared so as to satisfy the condition of InI mass:SnCl₂ mass = 1:2. The composition of the dielectric of Example 19 was determined by XPS analysis in the same manner as in Example 1. The dielectric of Example 19 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0147] <Example 20>
[0148] A powdered dielectric of Example 20 was produced in the same manner as in Example 1, except that raw material powders containing InI and SnI2 were prepared so as to satisfy the ratio of InI:SnI2 = 1:2. The composition of the dielectric of Example 20 was determined using XPS analysis in the same manner as in Example 1. The dielectric of Example 20 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0149] <Comparative Example 1>
[0150] A powdered dielectric of Comparative Example 1 was produced in the same manner as in Example 1, except that a raw material powder containing CsCl and PbCl₂ was prepared so as to satisfy the condition of CsCl:PbCl₂ mass = 1:1. The composition of the dielectric of Comparative Example 1 was determined by XPS analysis in the same manner as in Example 1. The dielectric of Comparative Example 1 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0151] <Comparative Example 2>
[0152] A powdered dielectric of Comparative Example 2 was produced in the same manner as in Example 1, except that a raw material powder containing (CH3NH3)Cl and SnCl2 was prepared so as to satisfy the condition of (CH3NH3)Cl:SnCl2 = 1:1. The composition of the dielectric of Comparative Example 2 was determined by XPS analysis in the same manner as in Example 1. The dielectric of Comparative Example 2 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1. Furthermore, crystal structure analysis was performed on the dielectric of Comparative Example 2 in the same manner as in Example 1. Figure 8 Graph showing the XRD pattern of the dielectric of Comparative Example 2. The horizontal axis represents the diffraction angle 2θ, and the vertical axis represents the intensity of X-ray diffraction. Figure 8 The calculated results of XRD patterns of perovskite-type MASnCl3 and SnCl2 are shown in the figure. MA in MASnCl3 is methylamine ion (CH3NH3) + . Figure 8 The vertical axis in represents the relative relationship of diffraction intensities of each XRD pattern, and does not represent the relative relationship of diffraction intensities between different XRD patterns. The XRD pattern of the dielectric of Comparative Example 2 shows that the dielectric has a perovskite-type crystal structure.
[0153] <Comparative Example 3>
[0154] A powdered dielectric of Comparative Example 3 was produced in the same manner as in Example 1, except that raw material powders containing BaF2 and MgF2 were prepared so as to satisfy the condition of BaF2:MgF2 mass ratio of 1:1. The composition of the dielectric of Comparative Example 3 was determined by XPS analysis in the same manner as in Example 1. The dielectric of Comparative Example 3 was evaluated for relative permittivity and polarization in the same manner as in Example 1. The results are shown in Table 1.
[0155] As shown in Table 1, in the dielectrics of Examples 1 to 20, the ratio r of the number of cations to the number of anions satisfies the condition of 1 / 2 < r < 2 / 3, and the relative dielectric constant of the dielectrics of each example exceeds 40. On the other hand, the relative dielectric constants of the dielectrics of Comparative Example 1 and Comparative Example 2 with a ratio r of 2 / 3 are less than 40.0 at a frequency of 1 MHz. The relative dielectric constant of the dielectric of Comparative Example 3 with a ratio r of 1 / 2 is also low, less than 40. Therefore, the calculated value of the polarization of the dielectrics of Examples 1 to 20 is higher than the calculated value of the polarization of the dielectrics of Comparative Examples 1 to 3. From the above, it is shown that a dielectric containing a halide and having a ratio r of the number of cations to the number of anions satisfying the condition of 1 / 2 < r < 2 / 3 easily has a high relative dielectric constant.
[0156] It is shown by Figure 7 and Figure 8 that the dielectric of Example 1 has a crystal structure of (NH4)Pb2Br5 type, and the dielectric of Comparative Example 2 has a perovskite type crystal structure. Figure 9 FIG. is a diagram showing the crystal structure of perovskite type (CH3NH3)SnCl3. Figure 10 FIG. is a diagram showing the crystal structure of KSn2Cl5 of (NH4)Pb2Br5 type. As Figure 9 shown, in the crystal structure of (CH3NH3)SnCl3, the coordination number of Cl 2+ around Sn - is 6. On the other hand, as Figure 10 shown, in the crystal structure of KSn2Cl5 of (NH4)Pb2Br5 type, the coordination number of Cl 2+ around Sn - is 8. Thus, the coordination number of anions relative to cations in the dielectric of Example 1 is more than the coordination number of anions relative to cations in the dielectric of Comparative Example 2. It is considered that this is one of the reasons why the relative dielectric constant of the dielectric of Example 1 is higher than the relative dielectric constant of the dielectric of Comparative Example 2. If the ratio r of the number of cations to the number of anions in the halide satisfies the condition of 1 / 2 < r < 2 / 3, the coordination number of anions relative to cations in the dielectric easily becomes large, and the dielectric easily has a high relative dielectric constant.
[0157] Table 1
[0158]
[0159] Industrial Applicability
[0160] The capacitor of the present disclosure easily has a high electrostatic capacitance and is useful.
Claims
1. A capacitor comprising: A first electrode; A second electrode; and A dielectric disposed between the first electrode and the second electrode, The dielectric contains a halide and satisfies the condition of 1 / 2 < r < 2 / 3, In the condition, r is the ratio of the number of cations to the number of anions in the halide.
2. The capacitor according to claim 1, The dielectric satisfies the condition of 0.57 ≤ r ≤ 0.
61.
3. The capacitor according to claim 1, The cation contains ions of elements selected from at least one of Group 13, Group 14, and Group 15.
4. The capacitor according to claim 3, The cation has a lone pair of electrons.
5. The capacitor according to claim 1, The cation comprises a member selected from In + , Tl + ,Ge 2+ Sn 2+ , Pb 2+ , Sb 3+ and Bi 3+ At least one of .
6. The capacitor according to claim 1, The cation comprises a member selected from Li + 、Na + , K + , Rb + , Cs + 、In + and Tl + At least one of .
7. The capacitor according to claim 1, The dielectric has a composition represented by AB2X5, In the composition, A is selected from Li + 、Na + , K + , Rb + , Cs + 、In + and Tl + At least one of, B is selected from Sn 2+ and Pb 2+ At least one of X is selected from F - , Cl - Br - ,I - and SCN - At least one of .
8. The capacitor according to claim 1, The anion is selected from F - and Cl - At least one of .
9. A circuit comprising the capacitor according to any one of claims 1 to 8.
10. A circuit board comprising the capacitor according to any one of claims 1 to 8.
11. An apparatus comprising the capacitor according to any one of claims 1 to 8.
Citation Information
Patent Citations
Ferroelectric device and manufacture thereof
JP1998093031A
Ferroelectric memory device arranged by use of perovskite compound and method for manufacturing the same
JP2016171152A